2016
DOI: 10.1310/sci2016-00001
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Acceptability of Implementing Indirect Calorimetry Into Routine Clinical Care of Patients With Spinal Cord Injury

Abstract: Background:In the absence of reliable predictive equations, indirect calorimetry (IC) remains the gold standard for assessing energy requirements after spinal cord injury (SCI), but it is typically confined to a research setting. The purpose of this study is to assess the feasibility and acceptability of implementing IC into routine clinical care in an Australian SCI rehabilitation facility. Methods: Bedside IC (canopy hood) was performed, and patients completed an IC acceptability questionnaire (open-ended; y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
(42 reference statements)
1
3
0
Order By: Relevance
“…[42] adjusted BMR to fat-free mass before determining the relationship with adiponectin compared to the current work. Similar to previous studies, steady state was reached within 5 minutes from starting the test and the respiratory exchange ratio was within 0.7-0.9 with coefficient of variations of less than 10% for both VO 2 and VCO 2 across the last 15 minutes [29, 43]. Another study showed a positive relationship between mean VO 2 and adiponectin in able-bodied individuals [44].…”
Section: Discussionsupporting
confidence: 81%
“…[42] adjusted BMR to fat-free mass before determining the relationship with adiponectin compared to the current work. Similar to previous studies, steady state was reached within 5 minutes from starting the test and the respiratory exchange ratio was within 0.7-0.9 with coefficient of variations of less than 10% for both VO 2 and VCO 2 across the last 15 minutes [29, 43]. Another study showed a positive relationship between mean VO 2 and adiponectin in able-bodied individuals [44].…”
Section: Discussionsupporting
confidence: 81%
“…Our results confirm the possibility to measure REE whitin the first 10 min with both Q-NRG® and Quark RMR® in canopy mode, provided that a steady state has been reached and that the first 5 min of measurement are discarded. Face mask could be an alternative for use in those individuals who suffer from claustrophobia under the canopy hood [23]. However, our results showed that its use was not optimal especially in men whose REE tended to be overestimated by 8.2%.…”
Section: Discussionmentioning
confidence: 65%
“…The additional time required for indirect calorimetry assessment may also limit the routine use of this tool. However, in their small study, Nevin and colleagues 18 reported positive feedback regarding feasibility and patient acceptability. Also, protocols already exist for certain patient populations.…”
Section: Discussionmentioning
confidence: 98%